Peningkatan Kemampuan Dasar Mahasiswa Arsitektur Melalui Program Magang Di Biro Arsitek - I Wayan Darma Yasa; I Made Suryadi; I Wayan Dodik Yasa; Nyoman Ratih Prabandari; Ni Putu Ratih Pradnyaswari Anasta Putri (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Internship programs are very important to do in order to increase students' self-potential and train job readiness. This research is motivated by low job readiness. The effect of internship experience is knowledge or skills gained from internships in the business world or industry for a certain period of time. Preparing prospective graduates who are professional and competent in their fields is the most important aspect in implementing an internship program for students. This study aims to find out what are the effects and results obtained in the internship process for architectural students to enter the world of architecture. In the internship process, I got some learning about what kind of work is done at the architectural bureau (person-job fit) and company organizations (person-organization fit). After completing the internship, students are expected to be able to provide an opinion on the workings and scope of the internship company. so that these factors ultimately shape students' perceptions of their future career (person-career fit). This study uses primary data obtained by direct observation and interviews with managers and students about the current street vendors management.